2012
DOI: 10.1016/j.ajpath.2011.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Low-Level Expression of miR-375 Correlates with Poor Outcome and Metastasis While Altering the Invasive Properties of Head and Neck Squamous Cell Carcinomas

Abstract: Small, noncoding microRNAs (miRNAs) have been shown to be abnormally expressed in every tumor type examined. We used comparisons of global miRNA expression profiles of head and neck squamous cell carcinoma (HNSCC) samples and adjacent normal tissue to rank those miRNAs that were most significantly altered in our patient population. Rank Consistency Score analysis revealed miR-375 to have the most significantly lowered miRNA levels in tumors relative to matched adjacent nonmalignant tissue from the same patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
82
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(89 citation statements)
references
References 43 publications
5
82
1
1
Order By: Relevance
“…In this setting, reduced miR-375 expression could be a predictor of poor outcome (HR: 12.8, 95% CI: 3-49) and distant metastasis (HR: 8.7, 95% CI: 2-31) in head and neck squamous cell carcinomas. 47 Also, women with metastatic non-small-cell lung cancer had lower plasma miR-375 expression than those with non-metastatic non-small-cell lung cancer (P o 0.05). 45 However, miR-375 has only rarely been assessed in EC.…”
Section: Discussionmentioning
confidence: 99%
“…In this setting, reduced miR-375 expression could be a predictor of poor outcome (HR: 12.8, 95% CI: 3-49) and distant metastasis (HR: 8.7, 95% CI: 2-31) in head and neck squamous cell carcinomas. 47 Also, women with metastatic non-small-cell lung cancer had lower plasma miR-375 expression than those with non-metastatic non-small-cell lung cancer (P o 0.05). 45 However, miR-375 has only rarely been assessed in EC.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have reported that reduced expression of miR-375 could be a biomarker for HNSCC. 18,21,37 The expression levels of miR-375 were found to be lower in oral SCC patient oral rinse and saliva compared with those in healthy controls. 21 The expression ratio miR-221:miR-375 could be useful for distinguishing HNSCC from normal epithelium.…”
Section: Aberrant Expression and Functional Significance Of Mir-375 Imentioning
confidence: 99%
“…18 Another report showed that low miR-375 expression levels significantly correlated with cancer survival and distant metastasis. 37 In ESCC, plasma concentrations of miR-375 were shown to be significantly lower in ESCC patients than in controls. 38 Furthermore, low expression levels of miR-375 were significantly correlated with advanced stage, distant metastasis, poor overall survival and disease-free survival in ESCC patients.…”
Section: Aberrant Expression and Functional Significance Of Mir-375 Imentioning
confidence: 99%
“…Examples of microRNA evaluation in head and neck SCC include studies from our own institution (Childs et al 6 and Harris et al 7 ). The latter study used a unique bioinformatics approach.…”
Section: Single Nucleotide Polymorphism Arraysmentioning
confidence: 99%
“…Using this process, miR-375 was identified as the most consistently decreased transcript among head and neck SCC tumours, and low levels of miR-375 were associated with poor survival. 7 DNA methylation arrays Another major source of epigenetic regulation is via methylation of DNA. The addition of a methyl group to the 5' region of cytosines found in gene promoter regions typically causes a reduction of gene expression of the associated gene, and modifications are often found at clusters of CpG dinucleotides (commonly referred to as 'CpG islands').…”
Section: Single Nucleotide Polymorphism Arraysmentioning
confidence: 99%